Implementation of E-Learning Learning to Improve Student Achievement in Elementary Schools: Implementasi Pembelajaran E-Learning untuk Meningkatkan Prestasi Belajar Siswa di Sekolah Dasar - Siti Arofah; Nurdyansyah Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of the study was to determine whether the implementation of e-learning could improve student achievement in SD Muhammadiyah 2 Tulangan. This study uses descriptive qualitative research so that it can describe information data in accordance with facts with methods that can describe and provide an overview. The technique used in the study was all third grade students. From the research results obtained academic and non-academic assessments, using e-learning learning can improve student achievement. The results of the study indicate that e-learning can encourage student achievement. Highlights: The study aimed to determine the impact of e-learning on student achievement. Descriptive qualitative research was employed to provide an overview of the data. The results indicated that e-learning positively influenced student achievement. Keywords: e-learning, student achievement, descriptive qualitative research, academic, non-academic assessments.